Exploration of Experience and Perception in Using Gradient Map for Digital Coloring - Sentani, Elizabeth Jessica; Yoo, Min-Hyuk; Sitinjak, Eunike Yolanda Zefanya; Kolombuto, Laura Gebrimova; Siahaan, Abigail Tamba; Susanto, Giovani (Universitas Multimedia Nusantara, 2025)
This study explores the experience and perception of using Gradient Map (GM) compared to the Direct Coloring (DC) method for digital coloring, particularly among learners. The research addresses whether GM provides benefits in four areas, learning curve, speed, ease of use, and satisfaction for users, and compared with the DC method. The research employed a mixed-methods approach involving comparative experiments using a within-subjects design and a post-experiment survey among 19 participants with varying experience. The experiment required participants to color an image using both GM and DC methods. Results show a near-even split in preference (52.6% for GM, 47.4% for DC), with the majority (84.2%) agreeing that GM is useful. However, the DC method scored slightly better on average for perceived learning curve and speed, and significantly higher for user satisfaction. The GM method was only marginally better in ease of use. GM's benefits include non-destructive editing and fast color experimentation, but its perceived drawbacks relate to the technicality, the multi-step process (value-first), and the need for pre-existing knowledge of value and color theory. In conclusion, GM is a powerful, efficient tool for color editing and experimentation, but its full benefit is realized when users already understand value and color theory. DC offers greater satisfaction and perceived ease of learning due to its directness. Future research should involve a larger, more diverse sample, and incorporate quantitative usability tests focusing on user experience. Keywords: gradient map; digital painting; digital colorization; direct coloring; user experience.